Nonhost resistance to rust pathogens – a continuation of continua - Bettgenhaeuser, Jan; Gilbert, Brian; Ayliffe, Michael; Moscou, Matthew J. (Frontiers in Plant Science, 2014)
The rust fungi (order: Pucciniales) are a group of widely distributed fungal plant pathogens, which can infect representatives of all vascular plant groups. Rust diseases significantly impact several crop species and considerable research focuses on understanding the basis of host specificity and nonhost resistance. Like many pathogens, rust fungi vary considerably in the number of hosts they can infect, such as wheat leaf rust (Puccinia triticina), which can only infect species in the genera Triticum and Aegilops, whereas Asian soybean rust (Phakopsora pachyrhizi) is known to infect over 95 species from over 42 genera. A greater understanding of the genetic basis determining host range has the potential to identify sources of durable resistance for agronomically important crops. Delimiting the boundary between host and nonhost has been complicated by the quantitative nature of phenotypes in the transition between these two states. Plant-pathogen interactions in this intermediate state are characterized either by (1) the majority of accessions of a species being resistant to the rust or (2) the rust only being able to partially complete key components of its life cycle. This leads to a continuum of disease phenotypes in the interaction with different plant species, observed as a range from compatibility (host) to complete immunity within a species (nonhost). In this review we will highlight how the quantitative nature of disease resistance in these intermediate interactions is caused by a continuum of defense barriers, which a pathogen needs to overcome for successfully establishing itself in the host. To illustrate continua as this underlying principle, we will discuss the advances that have been made in studying nonhost resistance towards rust pathogens, particularly cereal rust pathogens.